Evaluating Policy Rules Under Imperfect Credibility - Masson, Paul (IMF Working Papers; Working Paper ;, 1991)
Evaluation of policy rules using empirical macroeconomic models is usually done on the assumption that the rules are perfectly credible. However, there are usually circumstances that cause the authorities to abandon any given rule. The public's expectations reflect this possibility. In the paper, credibility is assumed to depend on the probability that the authorities will abandon a rule because the resulting utility exceeds that from maintaining the rule. Simulations of a disinflation policy leading to price stability are presented. Its credibility varies over time, depending on the paths for output and inflation.